Water properties and marinade uptake in broiler pectoralis major with the woody breast condition. (15th October 2022) - Zhang, Jian; Bowker, Brian; Yang, Yi; Pang, Bin; Yu, Xiang; Tasoniero, Giulia; Zhuang, Hong
Highlights: WB reduced marinade uptake by meat in the presence of salts. WB inhibited increases in intra-myofibrillar water mobility in marination. WB inhibited salt-induced water gain in intra-myofibrillar water. WB reduced increases in extra-myofibrillar water in salt-phosphate marination. Both intra- and extra-myofibrillar water are related to WB marinade uptake. Abstract: To provide insight into the mechanisms by which the woody breast (WB) condition reduces marinade uptake, water properties of normal (NOR) and WB meat were investigated using TD-NMR. Broiler Pectoralis major was marinated with either water, 0.625% sodium tripolyphosphate, 5% NaCl, or 5% NaCl + 0.625% sodium tripolyphosphate (SP). Targeted final concentrations were 4% NaCl and 0.5% SP. WB reduced meat marinade uptake but did not affect relationships between marinade ingredients and water mobility. WB inhibited increases in extra-myofibrillar water mobility induced by marinade ingredients. Marination increased intra-myofibrillar water (Amp21 ) regardless of marinade ingredients or muscle condition; however, WB resulted in reduced Amp21 . Additionally, NaCl- or phosphate-induced extra-myofibrillar water (Amp22 ) gain in WB was greater than that in NOR. Our data suggest changes in both Amp21 and Amp22 are related to the difference in marinade uptake between NOR and WB meat marinated with NaCl-phosphate marinade.